Climate trauma from wildfire exposure impacts cognitive decision-making - Jason Nan; Satish Jaiswal; Dhakshin Ramanathan; Mathew C. Withers; Jyoti Mishra (Scientific Reports)
Abstract Climate trauma refers to the chronic mental health sequalae of climate disaster events. We have previously shown evidence for such trauma with accompanying anxiety and depression symptoms after California’s 2018 Camp Fire wildfire. Here, we investigate whether this climate trauma also impacts cognitive decision-making and its neural correlates. One year after the wildfire, we recruited three groups - those directly exposed (n = 27), indirectly exposed (community members who witnessed the wildfire but not directly exposed, n = 21), versus non-exposed controls (n = 27). Participants performed a decision-making task that led to immediate and cumulative point rewards on each trial with simultaneous electroencephalography (EEG) recordings. We evaluated Win-Stay behavior in choosing to stay with the greater expected value (cumulative reward) option. Directly-exposed individuals showed significantly reduced Win-Stay behavior relative to the other groups. EEG analyses showed significantly greater parietal alpha activity for the selected choice and ensuing rewards in directly fire-exposed individuals, with an underlying cortical source of this activity in posterior cingulate cortex. Overall, these findings suggest that climate trauma may significantly impact neuro-cognitive processing in the context of value-based decision-making, which may serve as a useful biomarker target for future mental health interventions in climate change impacted communities.